Serum nesfatin-1 levels in patients with different glucose tolerance levels - Algul, S; Ozkan, Y; Ozcelik, O (Physiological research, 2016)
The aim of this study was to compare the levels of nesfatin-1 in healthy subjects with those in prediabetic and diabetic patients who have different glucose tolerance levels. Overall, 100 subjects were divided into 5 groups healthy control (C), impaired fasting glycemia (IFG), impaired glucose tolerance (IGT), metabolic syndrome (MS) and type 2 diabetes mellitus, (Type 2 DM). Glycated hemoglobin (HbA1c) assessed the glycemic control. Homeostasis model assessment of insulin resistance (HOMA-IR) was determined using computer analyses. Nesfatin-1 levels were measured using ELISA method. IFG and IGT (prediabetic groups) from MS and Type 2 DM (diabetic groups) differed significantly in HOMA-IR. The nesfatin-1 levels were lower, although not statistically significant, in IFG (0.937+/-0.03 ng/ml, p=0.07) and IGT (1.039+/-0.06 ng/ml, p=0.5) groups compared to healthy subjects (1.094+/-0.07 ng/ml). However, the nesfatin-1 levels were lower in patients with Type 2 DM (0.867+/-0.02 ng/ml, p=0.007) and MS (0.885+/-0.01 ng/ml, p=0.01) compared to healthy subjects. Nesfatin-1 levels were significantly lower in diabetic patients compared to healthy subjects. This study supports the role of insulin resistance in decreased nesfatin-1 levels in patients with Type 2 DM and MS.
Keywords: DNA vazebné proteiny; dospělí; Healthy Volunteers; glukózový toleranční test; Female; Nucleobindins; Adult; porucha glukózové tolerance; ženské pohlaví; Diabetes Mellitus, Type 2; zdraví dobrovolníci pro lékařské studie; Metabolic Syndrome; lidé; Blood Glucose; Glucose Tolerance Test; Prediabetic State; diabetes mellitus 2. typu; metabolický syndrom; proteiny nervové tkáně; nukleobindiny; Glycated Hemoglobin A; Humans; proteiny vázající vápník; Male; Nerve Tissue Proteins; Insulin Resistance; glykovaný hemoglobin; inzulinová rezistence; DNA-Binding Proteins; Glucose Intolerance; mužské pohlaví; krevní glukóza; Glycated Hemoglobin; prediabetes; Calcium-Binding Proteins